1989
DOI: 10.1007/bf01967297
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic modulation of TNF production by endotoxin stimulated macrophages:In vitro andin vivo effects of auranofin and other chrysotherapeutic compounds

Abstract: The gold compounds, auranofin, sodium aurothiomalate, and triethyl gold phosphine have been demonstrated to inhibit various effector functions associated with monocyte-macrophage populations. Incubation of human peripheral blood monocytes and murine peritoneal macrophages with auranofin or triethyl gold phosphine inhibited TNF production in lipopolysaccharide [LPS] stimulated murine peritoneal macrophages. The inhibitory effect of auranofin and triethyl gold phosphine on LPS stimulated monokine production was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Recently, it has been shown that SAT will accelerate the in vitro maturation of MONO to MAC with a concomitant decrease in IL-1 production. '2 13 Thus there is now the possibility to relate the therapeutic benefit with changes in expression of cytokines and the relative contribution of inflammatory MONO and downregulatory MAC within the synovial cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that SAT will accelerate the in vitro maturation of MONO to MAC with a concomitant decrease in IL-1 production. '2 13 Thus there is now the possibility to relate the therapeutic benefit with changes in expression of cytokines and the relative contribution of inflammatory MONO and downregulatory MAC within the synovial cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Elevations in serum TNF or IL-1 or both have been demonstrated in patients with septic shock, lupus, rheumatoid arthritis, parasitic infections, and cancer and in burn models (1, 7, 13, 17, 22-24, 32, 36, 40) and in animal models of endotoxinor bacterium-induced shock (6,9,11,16,25,37,39,43,46). While regulation of TNF and IL-1 by exogenous glucocorticoids (5,9,39,43,46), prostaglandin E2 (19,31), protein kinase C antagonists (18), and gold salts (10) has been reported, the role of endogenous mediators in regulating IL-1 and TNF synthesis is less clear. The ability of IL-1 and TNF to stimulate pituitary adrenocorticotropin secretion and the resulting release of corticosterone by the adrenals have suggested a role for the neuroendocrine axis in modulating cytokine production (2-4, 30,33,38,46).…”
mentioning
confidence: 99%
“…The above results contradict some reports in the literature that showed aurothiomalate has a small inhibitory effect on LPS-induced TNF production in human PBMCs. [71][72][73] A possible explanation for this difference could be that the experiments described here were performed using a murine macrophage cell line, as opposed to PBMCs isolated directly from humans [72,73] or mice. [71] It could also arise from differences in methodology, such as differences in the length of the pre-incubation period, and use of different LPS concentrations.…”
Section: Tumour Necrosis Factor Releasementioning
confidence: 99%
“…[71][72][73] A possible explanation for this difference could be that the experiments described here were performed using a murine macrophage cell line, as opposed to PBMCs isolated directly from humans [72,73] or mice. [71] It could also arise from differences in methodology, such as differences in the length of the pre-incubation period, and use of different LPS concentrations. [71][72][73] It should also be noted, however, that within the literature there are reports that suggest that aurothiomalate has no effect on production of TNF.…”
Section: Tumour Necrosis Factor Releasementioning
confidence: 99%
See 1 more Smart Citation